The Importance of Material Used in Speech Therapy: Two Case Studies in Minimally Conscious State Patients - Alice Sautet; Laura Hurtado; Anna Fiveash; Leslie Baron; Mélaine De Quelen; Fabien Perrin (Brain Sciences, 2022)
Speech therapy can be part of the care pathway for patients recovering from comas and presenting a disorder of consciousness (DOC). Although there are no official recommendations for speech therapy follow-up, neuroscientific studies suggest that relevant stimuli may have beneficial effects on the behavioral assessment of patients with a DOC. In two case studies, we longitudinally measured (from 4 to 6 weeks) the behavior (observed in a speech therapy session or using items from the Coma Recovery Scale—Revised) of two patients in a minimally conscious state (MCS) when presenting music and/or autobiographical materials. The results highlight the importance of using relevant material during a speech therapy session and suggest that a musical context with a fast tempo could improve behavior evaluation compared to noise. This work supports the importance of adapted speech therapy for MCS patients and encourages larger studies to confirm these initial observations.